Partisipasi Masyarakat Pada Pengelolaan Banjir Kota Gorontalo - Mohammad Sofyan; Soleh Soleh (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2018)
The community and several agencies the city of Gorontalo especially those directly related to the presence of the Bolango river show that their not to their satisfaction of the work because the community considers the work performed by the subproject has not been completed. The benefits in terms of flood control projects that were considered less been of more benefit value. Indeed, if the making embankments can be solved, then the value of benefits from the existence of the project will be very high because the area is secured a growing urban region that is generally a business district/trading area.